2019
DOI: 10.1108/mbr-01-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Building R&D capability in subsidiaries – conceptualization of a process perspective

Abstract: Purpose The purpose of this paper is to contribute to the literature discussing the internationalization of research and development (R&D) among multinational companies by proposing a process description to capture the development of local R&D capabilities in subsidiaries. Design/methodology/approach The authors build the conceptualization not only on the prevailing literature on resource management, subsidiary evolution and subsidiary initiatives, but also on empirical observations. Findings A pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…When subsidiaries operate in the host country’s market, they often need to improve their performance through cooperation. According to Lagerström et al (2019), a subsidiary identifies an opportunity in the host country that triggers the establishment of specific capabilities. The second stage is the gathering of support and resources from the host market and from MNEs internally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When subsidiaries operate in the host country’s market, they often need to improve their performance through cooperation. According to Lagerström et al (2019), a subsidiary identifies an opportunity in the host country that triggers the establishment of specific capabilities. The second stage is the gathering of support and resources from the host market and from MNEs internally.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on foreign direct investment in MNEs’ activities has followed a rather static approach and has not emphasized the development and management of research and development (R&D) capabilities within a subsidiary. However, a phased process can be distinguished to describe the evolution of the leveraging of capabilities in subsidiaries (Lagerström et al , 2019). These capabilities induce subsidiaries to create better performance and they also increase the possibility of cooperation between subsidiaries.…”
Section: Introductionmentioning
confidence: 99%
“…Since Ronstadt's (1977, 1978) influential study, numerous researchers have suggested typologies for MNCs' foreign R&D units (Cantwell and Mudambi, 2005; Cantwell and Piscitello, 2000; Håkanson and Nobel, 1993; Jha et al , 2018; Kuemmerle, 1999b; Lagerström et al , 2019; Medcof, 1997; Pearce, 1989; Qi et al , 2014; Vrontis and Christofi, 2019). Though they have used differing terminologies, several studies have distinguished between two main types of local R&D units: (1) home base competence exploiting units and (2) home base augmenting (competence creating) units (e.g., Cantwell and Mudambi, 2005; Kuemmerle, 1999b).…”
Section: Internationalization Of Mncs' Randd Activities: An Evolutionary Perspectivementioning
confidence: 99%
“…Partly inspired by Ronstadt's (1977, 1978) seminal work, the above-mentioned categorizations' underlying assumption is that a foreign R&D subunit's role changes, and most likely improves, over time as the capabilities and technological resources of the unit evolve (Lagerström et al , 2019). Furthermore, the literature on MNCs' internationalization of R&D activities has also incorporated insights from the subsidiary evolution literature (Birkinshaw, 1997; Birkinshaw and Hood, 1998; Dörrenbächer and Gammelgaard, 2006) by relating subsidiaries' R&D mandate evolution to the drivers of subsidiary evolution – namely, headquarters (HQ) assignment, local environment adaptation and subsidiary choice (Birkinshaw and Hood, 1998; Paterson and Brock, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…MNC and EMNC literature agrees on the importance of external and internal knowledge linkages in firm technological competence creation (Andersson and Forsgren, 2000;Asmussen et al, 2009;Buckley and Munjal, 2017;Cantwell and Mudambi, 2005;Frost et al, 2002;Gupta and Govindarajan, 1991;Kotabe and Kothari, 2016;Lagerström et al, 2019;Luo and Tung, 2007;Mathews, 2006;Monteiro et al, 2008;Mudambi et al, 2014;Rugman and Verbeke, 2001;Tsai, 2001;Verbeke and Kano, 2015;Zhang et al, 2019). It provides a platform, through which we can evaluate EMNCs' external and internal knowledge flow patterns by benchmarking their counterparts from mature industrialized countries (MMNCs).…”
Section: Introductionmentioning
confidence: 99%